Determinan Kebijakan Dividen pada Perusahaan Subsektor Minyak, Gas, dan Batu Bara yang Terdaftar di BEI Tahun 2020-2023 - Shehan Permayo Pasa; Evi Yuniarti; M. Muhayin A. Sidik (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research was conducted to determine the effect of liquidity, profitability, leverage, and firm size on dividend policy in oil, gas, and coal subsector companies listed on the the Indonesia Stock Exchange (IDX) in 2020-2023. This research uses 4 independent variables in the form of liquidity which is measured by the current ratio, profitability which is measured by the return on assets, leverage which is measured by the debt to equity ratio, and firm size which is measured by ln.total assets. The dependent variable is dividend policy, measured using the dividend payout ratio. The population in this research is 85 oil, gas, and coal subsector companies registered on the IDX in 2020-2023. Sampling used purposive sampling technique. The total research sample was 14 companies with 56 financial report data tested using multiple linear regression analysis. The results of the research that has been conducted show that profitability has an effect on dividend policy, while liquidity, leverage, and firm size have no effect on dividend policy.